Cosine similarity-based algorithm for social networking recommendation - Shaha Al-Otaibi; Nourah Altwoijry; Alanoud Alqahtani; Latifah Aldheem; Mohrah Alqhatani; Nouf Alsuraiby; Sarah Alsaif; Shahla Albarrak (Institute of Advanced Engineering and Science, 2022)
Social media have become a discussion platform for individuals and groups. Hence, users belonging to different groups can communicate together. Positive and negative messages as well as media are circulated between those users. Users can form special groups with people who they already know in real life or meet through social networking after being suggested by the system. In this article, we propose a framework for recommending communities to users based on their preferences; for example, a community for people who are interested in certain sports, art, hobbies, diseases, age, case, and so on. The framework is based on a feature extraction algorithm that utilizes user profiling and combines the cosine similarity measure with term frequency to recommend groups or communities. Once the data is received from the user, the system tracks their behavior, the relationships are identified, and then the system recommends one or more communities based on their preferences. Finally, experimental studies are conducted using a prototype developed to test the proposed framework, and results show the importance of our framework in recommending people to communities.